The effect of human resource development on the productivity of members of the Binjai City multi-business cooperative (KSU) source of Sustenance - Zainal, Zainal; Lumban Tobing, Surya Sevi Wijayanna; Azim, Fauza (Junal Ilmu Manajemen, 2025)
The purpose of the research is to determine the influence of human resource development on the productivity of members of the Binjai City Multi-Business Cooperative (KSU). This type of research is a quantitative descriptive research, with a simple linear regression analysis method. The population of this study is 43 respondents. Data collection techniques through interviews, questionnaires and documentation studies. The statement instrument is measured by the Likert scale. The results of the study show that the development of human resources has a positive and significant effect on the productivity of members of the Multi-Business Cooperative (KSU) Sumber Rezeki Binjai City by 53.8%.